RANCANG BANGUN SISTEM INFORMASI SEBARAN DISTRIBUSI KIS PROVINSI SULAWESI TENGGARA BERBASIS WEB - Fahrul Ardian Nugroho; Dini Fadilah; Chintya Mawadhah Sumitro; Rizal Adi Saputra (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2022)
Information technology and telecommunications have promoted the development in all fields, including in the service sector, which now almost all have internet facilities. BPJS Health itself has developed various technology-based innovations to support the implementation of JKN-KIS Program. One of them is the design of an information system for KIS distribution in Southeast Sulawesi. The KIS distribution system is intended to make it easier for BPJS Health employees or parties to see the distribution of KIS in districts/cities in Southeast Sulawesi. In order to get the expected results of this research, the making of this system used the prototype method. The prototype method is a method where developers and customers can interact with each other during the system creation process. In the testing phase, the method used is Black Box Testing. Black Box Testing performs testing without detailed knowledge of the internal structure of the system or component being tested. As a result, this study proves that this system can reduce errors that can occur when distributing KIS to every area in Kendari City, help and make it easier for BPJS membership workers to see the distribution of healthy Indonesia card data, as well as it can directly update.